No Evidence for an Association Between the Chemokine Receptor 5 Δ32 Polymorphism and Multiple Sclerosis Susceptibility: A Meta-Analysis: CCR5-Δ32 and MS, meta-analysis - Akbari, Nazanin; Saadat, Mostafa (Scripta Medica, 2025)
Background/Aim: Numerous reports have been published on the association of the chemokine receptor 5 Δ32 genetic variation (rs333) with the risk of multiple sclerosis (MS), with results that are inconsistent. The relationship between rs333 and susceptibility to MS was evaluated in this study.Methods: The PRISMA guidelines were followed in the current study. Twelve databases were used to find eligible articles. The investigators extracted the necessary information. The associations of the alleles and genotypes were evaluated in different models of inheritance: co-dominant, dominant and recessive genotype models and allele model.Results: The analysis included 14 articles reporting 16 studies involving 3265 MS patients and 3735 healthy controls. There was no substantial heterogeneity between studies for any of the comparisons. The significance level was not reached for the association between rs333 and MS susceptibility. Conclusion: The findings of this study could not confirm the relationship between the rs333 and susceptibility to multiple sclerosis.